Cost Effectiveness of Bosentan for Pulmonary Arterial Hypertension: A Systematic Review - Ruxu You; Xinyu Qian; Weijing Tang; Tian Xie; Fang Zeng; Jun Chen; Yu Zhang; Jinyu Liu (Canadian Respiratory Journal)
Objectives. Although many studies have reported on the cost-effectiveness of bosentan for treating pulmonary arterial hypertension (PAH), a systematic review of economic evaluations of bosentan is currently lacking. Objective evaluation of current pharmacoeconomic evidence can assist decision makers in determining the appropriate place in therapy of a new medication. Methods. Systematic literature searches were conducted in English-language databases (MEDLINE, EMBASE, EconLit databases, and the Cochrane Library) and Chinese-language databases (China National Knowledge Infrastructure, WanFang Data, and Chongqing VIP) to identify studies assessing the cost-effectiveness of bosentan for PAH treatments. Results. A total of 8 published studies were selected for inclusion. Among them were two studies comparing bosentan with epoprostenol and treprostinil. Both results indicated that bosentan was more cost-effective than epoprostenol, while the results of bosentan and treprostinil were not consistent. Four studies compared bosentan with other endothelin receptor antagonists, which indicated ambrisentan might be the drug of choice for its economic advantages and improved safety profile. Only two economic evaluations provided data to compare bosentan versus sildenafil, and the results favored the use of sildenafil in PAH patients. Four studies compared bosentan with conventional, supportive, or palliative therapy, and whether bosentan was cost-effective was uncertain. Conclusions. Bosentan may represent a more cost-effective option compared with epoprostenol and conventional or palliative therapy. There was unanimous agreement that bosentan was not a cost-effective front-line therapy compared with sildenafil and other endothelin receptor antagonists. However, high-quality cost-effectiveness analyses that utilize long-term follow-up data and have no conflicts of interest are still needed.